OBSOLESCENCE OF LITERATURE IN ZOOLOGY - Vimala, V.; Pulla Reddy, V. (Malaysian Journal of Library and Information Science, 1997)
Obsolescence of literature helps the librarians to maintain the need-based collection of literature. The study attempts to examine the obsolescence of literature in zoology by citation analysis. Citations from 128 doctoral theses in zoology submitted to Sri Venkateswara University, Tirupati, India, during the period 1962-1994 forms the basis for the study. It is observed that the citation frequency follows a negative exponential pattern. Half-life of literature is found to be 13 years for journal citations and 13.27 years for book citations.